Study Of The Needs Of Parking Spaces Traffic Controller In Campus Of Universitas Muhammadiyah Surakarta - Rosdiyani, Telly; , Nurul Hidayati, ST., MT., Ph.D; , Gatot Slamet SM, MT (2016)
Abstract: the increasing number of students caused the amount of movement that is on any Campus. This of course requires the improvement of infrastructures of the movement of vehicles and people on campus. This research aims to know the characteristics of the offender and the parking lot, parking space requirements of current and future alternative, identify the type of parking policy can be conducted on campus. The process of data retrieval is done by recording the vehicle backwards with time, and spread the question form/questionnaire offender users vehicles parking, parking space requirements the future predicted by the regression model. The results of the analysis showed the highest volume motorcycle parking happen in D (3296 vehicles), whereas the car in the A-C (535 vehicles). The value of the accumulated the highest motorcycle parking happen in D (965 kend/15 minutes), while the car in the A-C (153 kend/15 minutes). The average duration of the longest parking (4.17) occur in G (motorcycles), the value of the index indicates the majority of parking the parking location was not capable of holding the vehicle parking. The current parking space requirements most occur in E (788 SRP motor) while for the cars going in A-C (162 SRP car). The majority of respondents came from Sukoharjo, trip duration 25-30 minutes to travel 1 time daily to the campus, by driving a motorcycle. The proposed model to predict the SRP 5 years into the future relationship between the number of compartments parking (Y2) and the number of vehicles (X2) is Y2 = 54.70 0, 42x2. This model has the value R square of 0.75, with the number of vehicles 22,858 vehicles, parking space requirements 9,609 swath of parking. Identification of the type of policy respondents as principals the policies allow students/faculty/employees bringing personal vehicles to campus with the requisite home/kost far from campus, parking policy systems use of vehicle registration vehicle to exit the parking area and the type of policy to control the number of vehicles bicycle loan facilities on campus.